ANALISIS RAGAM TEKS DESKRIPTIF BERBANTUAN MEDIA GAMBAR DI SEKOLAH DASAR - Muhamad Faisal Rahmadiyana, Faisal Rahmadiyana (2022)
The skill of writing description texts is the basis of learning at the elementary school one of which is by writing description texts. However, in the current conditions, students are less courageous and less thorough in expressing their thoughts, feelings and experiences through their writing.This study aims to find out the skills of writing descriptions through the medium of picture, due to the possibility of increasing the reasoning and thinking skills of students. In this study, students were assigned to determine the main topic and explain the creation of a description text essay through picture, then the results were analyzed. The method used in this study is qualitative descriptive analysis. After the entire series of research is carried out, the results of this study describes the analysis of the skills of writing description texts made by students through the medium of image based on aspects of writing stages, inculding (1) Writing the main topic (2) writing an explanatory topic, also accompanied by the structure of writing a description text. Based on the findings of the research results from 10 student participants, it showed that the students were not considered sufficient to obtain results in the very good category, however, some students showed results in the good category, and the moderate category. The obstacles faced by students in writing description text essays, students still feel confused in determining the main topic and correct explanation in the image media. Keywords: Description Text; Instructional Media, Picture